1994
DOI: 10.1139/v94-004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative radical cyclization to pyrroles under reducing conditions. Reductive desulfonylation of α-sulfonylpyrroles with tri-n-butyltin hydride

Abstract: , 15 (1994) 1-(2-Bromobenzy1)-2-alkanesulfonylpyrroles (lc, 16) and 1-(4-bromobuty1)-2-methylsulfonfylpyrrols (8) undergo oxidative radical cyclization with partial or complete reductive desulfonylation to the pyrrolizidine derivatives 5 and 9 by an AIBN initiated reaction with tri-n-butyltin hydride. These cyclizations are suggested to proceed via a pseudo SRNl process involving radical addition to the a position of the pyrrole nucleus not bearing the sulfonyl group. Reductive removal of the alkylsulfonyl m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Radical cyclisation onto heteroarenes has been developed in recent years to considerable advantage for the synthesis of novel polycyclic heteroarenes. Examples of these cyclisations include: a. alkyl radicals onto pyrroles, 8,9 imidazoles, 8 pyrazoles, 10 indoles, 9,11, 12 1,2,3-triazoles, 13 pyridinium salts, 14 and quinolones; 15 b. acyl radicals onto pyrroles, 16 quinolines, 17 pyridines 18 and arenes; 19 c. aryl radicals onto indoles, 20,21 pyrroles, 9 pyridones, 22 and 5-amino-and 5-hydroxyuracils, 23 2-quinolones, 24 quinolines 25 and pyridines. 26 All of the above cyclisations are 'oxidative' i.e.…”
mentioning
confidence: 99%
“…Radical cyclisation onto heteroarenes has been developed in recent years to considerable advantage for the synthesis of novel polycyclic heteroarenes. Examples of these cyclisations include: a. alkyl radicals onto pyrroles, 8,9 imidazoles, 8 pyrazoles, 10 indoles, 9,11, 12 1,2,3-triazoles, 13 pyridinium salts, 14 and quinolones; 15 b. acyl radicals onto pyrroles, 16 quinolines, 17 pyridines 18 and arenes; 19 c. aryl radicals onto indoles, 20,21 pyrroles, 9 pyridones, 22 and 5-amino-and 5-hydroxyuracils, 23 2-quinolones, 24 quinolines 25 and pyridines. 26 All of the above cyclisations are 'oxidative' i.e.…”
mentioning
confidence: 99%
“…To synthesize bis‐methylthioated vinylpyrroles 42 and 43 , 2‐methylthiopyrroles 36 and 37 were first acetylated using a Vilsmeier–Haack reaction, giving 2‐acetyl‐5‐methylthiopyrroles 38 and 39 (Scheme ) ; Muchowski et al . have demonstrated that the 5‐methylthio group has a directing effect to give acylation exclusively at the 2‐position.…”
Section: Resultsmentioning
confidence: 99%
“…Crude N ‐methyl‐2‐methylthio‐5‐acetylpyrrole 39 (9.15 g, 54.064 mmol, included approximately 13% 2‐ and 3‐acetyl‐ N ‐methylpyrrole by mass) was dissolved in THF (250 mL). Lawesson's reagent (26.24 g, 64.877 mmol) was added, and the mixture was stirred at RT for 3 h, at which time TLC indicated complete consumption of the starting materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…an oxidative process. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Most of the intermediate cyclised radicals are aromatic π-radicals which undergo rearomatisation by loss of hydrogen. The mechanism has been the subject of debate in the literature.…”
mentioning
confidence: 99%